2016
DOI: 10.1111/jhn.12434
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of physical activity, adipokines, vitamin D status and dietary vitamin D intake among adolescents

Abstract: Low PAL was associated with a lower A/L ratio. Vitamin D status was not associated with sun exposure habits, although it was positively correlated with vitamin D intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Physical activity and vitamin D status in preschool children in Kendari city were found to have no signifi cant relationship in this study. This study supports previous research (Giudici et al, 2017) that found no link between physical activity and serum vitamin D levels. The diff erent methods of assessing physical activity cause diff erences in the results of these studies (Wanner et al, 2015).…”
Section: Host Factors Social Demographics Vitamin D Intake Duration O...supporting
confidence: 92%
“…Physical activity and vitamin D status in preschool children in Kendari city were found to have no signifi cant relationship in this study. This study supports previous research (Giudici et al, 2017) that found no link between physical activity and serum vitamin D levels. The diff erent methods of assessing physical activity cause diff erences in the results of these studies (Wanner et al, 2015).…”
Section: Host Factors Social Demographics Vitamin D Intake Duration O...supporting
confidence: 92%
“…If our hypothesis of a causal role of adiponectin deficiency in the development of BPH is true, correcting adiponectin deficiency might bring about slowing of the prostate growing rate. In fact, adiponectin levels might be enhanced by increased physical activity, weight loss or dietary changes 51 52 . Recent epidemiological studies have reported that life-style factors such as increasing physical activity 53 , bariatric surgery 54 and intake of more vegetables and less high-fat food 55 appear to protect against the development of BPH-LUTS.…”
Section: Discussionmentioning
confidence: 99%